2015
DOI: 10.12659/ajcr.894206
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Recurrent Pyogenic Bilateral Psoas Abscess Causing Bilateral Pulmonary Embolism by Iliac Vein Compression

Abstract: Patient: Male, 47Final Diagnosis: Bilateral psoas abscess • acute lower extremity deep vein thrombosis • bilateral pulmonary embolismSymptoms: Progressive left leg swelling • productive cough with whitish sputum • right flank painMedication: Antibiotics and anticoagulationClinical Procedure: CT-guided percutaneous drain placementSpecialty: Internal Medicine/Critical CareObjective:Unusual presentationBackground:Psoas abscesses are a known cause of back pain, but they have not been reported as a cause of acute l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Few cases of psoas abscess resulting in iliofemoral venous thrombosis have been reported [4], [5], [6], [7], [8]. We report a rare case of paraspinal abscess causing IVC thrombus, and the first as a result of viridans infection.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Few cases of psoas abscess resulting in iliofemoral venous thrombosis have been reported [4], [5], [6], [7], [8]. We report a rare case of paraspinal abscess causing IVC thrombus, and the first as a result of viridans infection.…”
Section: Discussionmentioning
confidence: 92%
“…Psoas and paravertebral abscesses, as a complication of osteomyelitis, are frequently associated with Pott’s disease; however, pyogenic vertebral osteomyelitis can also result in formation of these abscesses [3]. Such intra-abdominal collections can in rare occasions cause compression of adjacent venous structures and result in deep vein thrombosis [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Delay in diagnosis and treatment of iliopsoas abscess leads to multiple complications, including sepsis, septic arthritis, deep venous thrombosis, and ileus [16][17][18]. Advanced age, bacteremia, and delay in treatment are associated with increased mortality [8,17].…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of psoas abscess due to TB can present with a range of symptoms, this study has shown that most cases presented with few symptoms and required diagnosis using computed tomographic (CT) or magnetic resonance imaging (MRI). Recent studies have highlighted the infectious complications of psoas abscess, but also the possibility of complete resolution [ 16 ]. Imaging studies have now contributed to the development of treatment protocols for abscesses due to TB [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%